Skills Shortage: A Critical Evaluation of the Use of Human Participants in Early Spear Experiments - Annemieke Milks (EXARC, 2019)
Hand-delivered spears are the earliest clear hunting technology in the archaeological record, with origins from 400,000 years ago, before the evolution of our own species. Experimental archaeological approaches to early weaponry continue to grow, and both controlled and naturalistic experiments are making significant contributions to interpreting such technologies. Using human participants is often useful and sometimes necessary for such work. This paper argues that greater consideration should be afforded to a number of aspects of human performance in experimental work - whether naturalistic or controlled - including how proficiency and physiology may affect outcomes.